DETEKSI GEN OXA-51 DAN OXA 58 PENANDA RESISTENSI KARBEPENEM PADA ISOLAT Acinetobacter baumannii DAN UJI KEPEKAANNYA TERHADAP ANTIBIOTIK MEROPENEM DAN IMIPENEM - Ardy Prian Nirwana; Vector Stephen Dewangga; Erika Wulandari (LPPM Universitas Abdurrab, 2025)
Acinetobacter baumannii (Carbapenem Resistant Acinetobacter baumannii CRAB) is a bacterium that is resistant to almost all antibiotics and is difficult to eliminate from the environment. Some CRABs can carry genes that allow bacteria to make carbapenemase enzymes that destroy carbapenem antibiotics. These carbapenemase genes can move between bacteria, increasing the possibility of spreading resistance to various drugs. Commonly detected genes are the oxacillinase group such as OXA-23, ΟΧΑ-24/40, ΟΧΑ-51 and OXA-58. A small portion of CP-CRAB has a mobile gene that encodes carbapenemase which is often found in other gram-negative bacteria, such as Enterobacterales. This study aims to detect whether the OXA-51 and OXA-58 genes are detected in Acinetobacter baumannii isolates, which are genes encoding molecular indicators of resistance to the carbapenem group. The study design was an observational analytical study with a cross-sectional approach. The target population was all Acinetobacter baumannii cultures. From the research results, the sensitivity test showed that all samples were resistant to meropenem and imipenem antibiotics, while the DNA isolation process that had been carried out needed to be optimized to obtain the right isolation procedure in order to obtain clear DNA band visualization results and visualization of the OXA-51 gene showed optimal results, while detection of the OXA-58 gene still needed optimization to be more sensitive and specific. The output of the research for publication has cannot been done yet because the research will be continued to the next stage.